2017
DOI: 10.1186/s13046-017-0597-y
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar and spindle associated protein 1 promotes the aggressiveness of astrocytoma by activating the Hedgehog signaling pathway

Abstract: Background: The prognosis of human astrocytoma is poor, and the molecular alterations underlying its pathogenesis still needed to be elucidated. Nucleolar and spindle associated protein 1 (NUSAP1) was observed in several types of cancers, but its role in astrocytoma remained unknown. Methods:The expression of NUSAP1 in astrocytoma cell lines and tissues were measured with western blotting and Real-Time PCR. Two hundred and twenty-one astrocytoma tissue samples were analyzed by immunochemistry to demonstrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 53 publications
1
58
0
Order By: Relevance
“…Okamoto et al revealed high NUSAP1 expression was related to more advanced T stage and inhibiting NUSAP1 resulted in the suppression of cell proliferation in Oral Squamous Cell Carcinoma (OSCC). Similar biological functions of NUSAP1 were also observed in other malignancies, including breast cancer, hepatocellular carcinoma (HCC), glioblastoma multiforme (GBM), colorectal cancer, astrocytoma, glioma, renal cell carcinoma, and prostate cancer . And previous studies also reported downregulating NUSAP1 could enhance the susceptibility to epirubicin in invasive breast cancer and the anti‐tumour effect of paclitaxel in OSCC .…”
Section: Introductionsupporting
confidence: 59%
“…Okamoto et al revealed high NUSAP1 expression was related to more advanced T stage and inhibiting NUSAP1 resulted in the suppression of cell proliferation in Oral Squamous Cell Carcinoma (OSCC). Similar biological functions of NUSAP1 were also observed in other malignancies, including breast cancer, hepatocellular carcinoma (HCC), glioblastoma multiforme (GBM), colorectal cancer, astrocytoma, glioma, renal cell carcinoma, and prostate cancer . And previous studies also reported downregulating NUSAP1 could enhance the susceptibility to epirubicin in invasive breast cancer and the anti‐tumour effect of paclitaxel in OSCC .…”
Section: Introductionsupporting
confidence: 59%
“…8 Similarly, high NUSAP1 expression levels promoted astrocytoma progression through the Hedgehog signaling pathway. 10 In addition, NUSAP1 is highly expressed in colon cancer tissues and cells, and NUSAP1 upregulation indicates a poor prognosis. 13 In colorectal cancer, NUSAP1 knockdown induced apoptosis and inhibited tumor cell migration, invasion, cell proliferation and EMT by inhibiting the expression of DNA methyltransferase 1 (DNMT1), indicating that NUSAP1 can be used as an independent prognostic biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Increased expression of NUSAP1 has been observed in many tumors, such as prostate cancer, acute myeloid leukemia, cervical cancer, oral squamous cell carcinoma, and astrocytoma, and NUSAP1 has been found to be closely associated with tumor progression. [6][7][8][9][10] However, the potential relationship between NUSAP1 expression in BLCA and clinical outcomes remains unknown and requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Nucleolar and spindle‐associated protein 1 (NUSAP1) is a microtubule‐binding protein and has been found to play important roles in mitotic spindle assembly . The expression of NUSAP1 is frequently increased in the proliferating cells, leading to microtubule bundling and G2/M phase arrest . Recently, reposts have demonstrated that NUSAP1 is strongly implicated in the tumorigenicity of several kinds of cancers, such as cervical carcinoma, breast cancer, and liver cancer .…”
Section: Introductionmentioning
confidence: 99%